Are Adverse Childhood Experiences Associated With Being in the System of Care? - Lackova Rebicova, Miriama; Dankulincova Veselska, Zuzana; Madarasova Geckova, Andrea; Jansen, Danielle E. M. C.; van Dijk, Jitse P.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2022)
Background Adverse childhood experiences (ACEs) can cause serious mental problems in adolescents and therefore may expected to be associated with higher use of psychosocial care, potentially varying by type of specific ACE. The aim of our study is to explore the association of the number of ACE and types of specific ACE with entering and using psychosocial care. Methods We used data from the Slovak Care4Youth cohort study, comprising 509 adolescents from 10 to 16 years old (mean age 13.2 years, 48.6% boys). We used logistic regression models adjusted for age, gender, and family affluence to explore the associations of number and type of specific ACE with the use of psychosocial care. Results Having three or more ACE as well as experiencing some specific ACE (death of a mother/father, death of somebody else you love, problems of a parent with alcohol or drugs, conflicts or physical fights between parents, and separation/divorce of parents) increased the likelihood of using psychosocial care. Regarding experience with the death of somebody else you love, we found a decreased likelihood of the use of psychosocial care. Conclusion Experiencing ACE above a certain threshold (three or more) and parent-related ACE increase the likelihood of adolescent care use.